Judgment and condemnation: How we love it!. Issue 1 (6th March 2018) - Peters, Ted
Abstract: The violence and death in Charlottesville on August 14, 2017 led to a national and even international barrage of condemnations of white supremacy along with condemnations of those who were slow to condemn. Why do we like to judge and condemn? And why do we do it with such passion and zeal? If the biblical gospel proclaims that we are justified before God by grace and not via self‐justification through condemnation, could we turn our attention more directly to those victimized by the conflict at hand? Specifically, could we listen to the voices of African Americans, Jews, America's Deep South, America's Southwest, and the disenfranchised white working class?